Teacher motivation: Definition, research development and implications for teachers - Han, Jiying; Yin, Hongbiao (Cogent education, 2016)
The past decade has witnessed an increase in research on teacher motivation which has been proved a crucial factor closely related to a number of variables in education such as student motivation, educational reform, teaching practice and teachers' psychological fulfilment and well-being. To address the constant calls for teacher motivation research, this paper attempts to pose a comprehensive review of teacher motivation studies conducted from diversified theoretical perspectives. Five research areas related to teacher motivation research have been identified: influencing factors of teacher motivation; teacher motivation and teaching effectiveness; teacher motivation and student motivation; teacher motivation research across different disciplines; and the instruments for assessing teacher motivation. Based on a critique of existing literature in terms of theoretical perspectives, research methodology, research content and concerns about contextual issues, potential directions for future research are finally proposed.